A multiscale investigation of reaction kinetics, phase formation, and mechanical properties of metakaolin geopolymers. (April 2017) - Zhang, Mo; Zhao, Mengxuan; Zhang, Guoping; El-Korchi, Tahar; Tao, Mingjiang
Abstract: A multiscale study is presented of the reaction kinetics, phase formation, mechanical properties of metakaolin-based geopolymers by varying Si/Al ratios of 1.2–2.2 and Na/Al ratios of 0.6–1.2. Macro- and nano-mechanical properties of geopolymer samples were determined by unconfined compression testing and grid nanoindentation technique, respectively. The latter, in combination with statistical deconvolution, also enables the extraction of generally 4 distinct phases together with their nanomechanical properties and volumetric fraction within the synthesized geopolymers. Moreover, the reaction kinetics, phase formation (particularly geopolymer gel development), and mechanical property development were investigated by characterizing geopolymers cured at the final setting time, 7, and 28 days. Phase formation was characterized by Fourier transform infrared spectroscopy (FTIR) via monitoring the evolution of the Si-O-T (T: Si or Al) and Al-O bonds. Results illustrate that the fraction of geopolymer gels dominantly governs the mechanical behavior, both of which increase with the Si/Al and Na/Al molar ratios, while the final setting time increases with the Si/Al ratio, but decreases with the Na/Al ratio. The chemical composition for the best mechanical performance of the studied geopolymers is a Si/Al ratio of 1.7 and Na/Al ratio of 0.9. The relationships among geopolymer chemical compositions, geopolymer gel formation rate, and macromechanical properties are also discussed.